Risk of New-Onset Atrial Fibrillation Post-cavotricuspid Isthmus Ablation in Typical Atrial Flutter Without History of Atrial Fibrillation - Li, Jia-hui; Xie, Hai-yang; Chen, Yan-qiao; Cao, Zhong-jing; Tang, Qing-hui; Guo, Xiao-gang; Sun, Qi; Ma, Jian (Frontiers in Physiology, 2021)
Aims: The aim was to describe the incidence of atrial fibrillation (AF) after cavotricuspid isthmus (CTI) ablation in patients with typical atrial flutter (AFL) without history of AF and to identify risk factors for new-onset AF after the procedure. Methods: A total of 191 patients with typical AFL undergoing successful CTI ablation were enrolled. Patients who had history of AF, structural heart disease, cardiac surgery, or ablation or who received antiarrhythmic drug after procedure were excluded. Clinical and electrophysiological data were collected. Results: There were 47 patients (24.6%) developing new AF during a follow-up of 3.3 ± 1.9 years after CTI ablation. Receiver operating characteristic (ROC) curves indicated that the cut-off values of left atrial diameter (LAD) and CHA2DS2-VASc score were 42 mm and 2, with area under the curve of 0.781 and 0.550, respectively. The multivariable Cox regression analysis revealed that obstructive sleep apnea (OSA) [hazard ratio (HR) 3.734, 95% confidence interval (CI) 1.470–9.484, P = 0.006], advanced interatrial block (aIAB) (HR 2.034, 95% CI 1.017–4.067, P = 0.045), LAD > 42 mm (HR 2.710, 95% CI 1.478–4.969, P = 0.001), and CHA2DS2-VASc score > 2 (HR 2.123, 95% CI 1.118–4.034, P = 0.021) were independent risk factors of new-onset AF. Conclusion: A combination of OSA, aIAB, LAD > 42 mm, and CHA2DS2-VASc > 2 was a strongly high risk for new-onset AF after ablation for typical AFL, and it had significance in postablation management in clinical practice.